Young children are not driven to explore imaginary worlds. (18th November 2022) - Nyhout, Angela; Lee, Ruth
Abstract: We address Dubourg and Baumard's claim that imaginary worlds are most appealing early in the lifespan when the exploratory drive is highest. Preschool-age children prefer fictions set in the real world, and fantastical information can be difficult for children to represent in real time. We speculate that a drive to explore imaginary worlds may emerge after children acquire substantial real-world skills and knowledge. An account of age effects on fictional preferences should encompass developmental change.